Analisis Kecurangan Laporan Keuangan Dengan Model Beneish M-Score Pada Sektor Kesehatan - Darmatika, Winingtias; Ramadhan, Yanuar; Arzeta, Davina; Isnaeni, Wirdatul; Syukriati, Selviana; Caprina, Tiffany (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The study aims to detect indications of financial statement manipulation using the Beneish M-Score model. The research population is the health sector listed on the Indonesia Stock Exchange in the period 2021-2023 with a total of 35 companies. The research sample was taken using purposive sampling method and obtained 14 companies with financial reports for 3 years, so there were 42 data used. The results of this study indicate that the Beneish M-Score model is able to detect indications of financial statement manipulation. It is known that there are 10 companies that are indicated to have manipulated financial statements in the 2021-2023 period. The percentage frequency of companies indicated as non-manipulators is 66.67%, gray areas are 4.76%, and manipulators are 28.57%. The results of this study contribute to the development of literature related to the detection of indications of financial statement manipulation, especially with the Beneish M-Score model and are expected to be useful for companies as a consideration in preventing financial statement manipulation practices.